Combining systems pharmacology, metabolomics, and transcriptomics to reveal the mechanism of Salvia miltiorrhiza-Cortex moutan herb pair for the treatment of ischemic stroke - Zhao, Chao; Bai, Xiaodan; Ding, Yi; Wen, Aidong; Fu, Qiang (Frontiers in Pharmacology, 2024)
Ischemic stroke (IS), predominantly triggered by blockages in cerebral blood flow, is increasingly recognized as a critical public health issue. The combination of Salvia miltiorrhiza (SM) and Cortex moutan (CM), traditional herbs in Eastern medicine, are frequently used for managing heart and brain vascular conditions. However, the exact mechanisms by which this herb pair (SC) combats IS remain largely unexplored. This investigation focuses on pinpointing the active constituents in SC that contribute to its protective role and deciphering the mechanisms countering cerebral ischemia, particularly in a middle cerebral artery occlusion (MCAO) rat model. We employed UPLC-Q-TOF-MS/MS alongside network pharmacology for predicting SC's target actions against IS. Key ingredients were examined for their interaction with principal targets using molecular docking. The therapeutic impact was gauged through H&E, TUNEL, and Nissl staining, complemented by transcriptomic and metabolomic integration for mechanistic insights, with vital genes confirmed via western blot. UPLC-Q-TOF-MS/MS analysis revealed that the main components of SC included benzoylpaeoniflorin, salvianolic acid B, oxypaeoniflora, salvianolic acid A, and others. Network pharmacology analysis indicated that SC's mechanism in treating IS primarily involves inflammation, angiogenesis, and cell apoptosis-related pathways, potentially through targets such as AKT1, TNF, PTGS2, MMP9, PIK3CA, and VEGFA. Molecular docking underscored strong affinities between these constituents and their targets. Our empirical studies indicated SC's significant role in enhancing neuroprotection in IS, with transcriptomics suggesting the involvement of the VEGFA/PI3K/AKT pathway and metabolomics revealing improvements in various metabolic processes, including amino acids, glycerophospholipids, sphingomyelin, and fatty acids metabolisms.